EXPERIENCIA Y POLÍTICA EN LA HISTORIA CONCEPTUAL (Res Publica. Revista de Historia de las Ideas Políticas, 2008)
My contribution is an attempt to examine the political background of Reinhart Koselleck’s Begriffsgeschichte, both in its metodological and theoretical aspects. This author has indicated the elective affinities between a conceptual history attached to the textual specific sources, from one side, and an epistemology of history with trascendental and extra-textual ambitions, from the other. A halfway position corresponds to the historical semantics, paradigmatically applied to the transition from Absolutism to the French Revolution. Habermas and the Cambridge School (Pocock and Skinner) have confronted the ideologically partial description of this step, and the metodology employed for it. According to Habermas, satanization of publicity and public opinion as casus belli, wich excludes both of them as principle of political rationality, reveals the schmittian filiation of Koselleck. The trascendental doctrine of history, the Historik, is conservative because it masks the interest of finding a continuity with the most fateful past of Germany. Pocock denounces the extrapolation of a methodology valid only for the German national culture, that is, the germanization of all the conceptual history. In front of the accelerated times of modernity, in wich the two main metahistoric categories —experience space and horizont of expectation— achieve, because their maximum assimetry, the greatest visibility, Koselleck aims to slow cautiously that frenetic rhythm with a balance between tradition and future. But Koselleck does not profit the potential of criticism and self-criticism implied in his contributions because his lack of will to questioning, in his own case, the dynamic tensions between concept and structure or the versatility of the notion of praxis (as hermeneutic application of sense, or as intervention at long-term in the world). The Begriffsgeschichte contains all the ingredients to the reflection on a public use of history or historic reason. In its public use, he would plead for a retrospective inquire on the meaning of an imputation of responsibilities, in a prospective search to come to a reciprocal understanding among the citizens.